2019
DOI: 10.11606/s1518-8787.2019053000705
|View full text |Cite
|
Sign up to set email alerts
|

Monotony in the consumption of fruits and vegetables and food environment characteristics

Abstract: OBJECTIVE: To analyze the quantity and diversity in the consumption fruits and vegetables, as well as its relationship with the consumer’s purchase characteristics and food environment. METHODS: Baseline study stemming from a controlled and randomized community trial investigating a sample representative of Primary Health Care services (Health Academy Program) of Belo Horizonte, state of Minas Gerais. The intake of fruits and vegetables was analyzed in servings/day, whereas diversity was assessed by the Food F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 18 publications
0
19
1
7
Order By: Relevance
“…Three studies included child participants [ 18 , 33 , 34 ] and four studies included adolescent participants [ 35 , 36 , 37 , 38 ]. Thirty-seven studies included adult participants [ 14 , 15 , 16 , 17 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 31 , 32 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]; seven studies included a combination of children or adolescents and adults [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies included child participants [ 18 , 33 , 34 ] and four studies included adolescent participants [ 35 , 36 , 37 , 38 ]. Thirty-seven studies included adult participants [ 14 , 15 , 16 , 17 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 31 , 32 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]; seven studies included a combination of children or adolescents and adults [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Falciglia et al (2005) found increased fruit variety intake among participants that received an intervention to increase FV consumption and improve dietary quality [ 32 ]. Additionally, increasing environmental FV variety could be a useful strategy to increase FV variety consumption; in a study examining FV variety consumption, purchasing characteristics, and food environment, de Deus Mendonça et al (2019) posited that greater fruit variety in commercial outlets would increase fruit variety consumption [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations